Sustainability and the art of long term thinking - Klauer, Bernd; Manstetten, Reiner; Petersen, Thomas; Schiller, Johannes (Routledge, 2017)
pt. I. Sustainability and time -- pt. II. The conceptual framework of stocks -- pt. III. Applying the stocks framework -- pt. IV. The art of of long-term thinking.
Includes bibliographical references (pages [223]-237) and index
Gesehen am 25.11.2020
Keywords: Electronic books; Nachhaltigkeit; Langfristige Prognose